Analisa Karakteristik Getaran Pada Mesin Stone Crusher Berdasarkan Kapasitas Pemecah Batu Koral 50 Ton/Jam Pada Daerah Horizontal, Vertikal dan Longitudinal Berdasarkan Time Domain - Sihombing, Suriady; Naibaho, Waldemar; Nababan, Wilson; Sinaga, Amran (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2023)
Stone Crusher Machine is one type of machine that is very popularly used among road construction in Indonesia, whether it is used for road or building transportation purposes where it is necessary to know how to analyze the vibration characteristics of the Stone Crusher machine based on the capacity of breaking coral in horizontal, vertical and longitudinal areas. based on the time domain. The research method is carried out by collecting data on the magnitude of the deviation, speed and acceleration that arise due to the process of breaking coral so that it produces several dimensions of the size of crushed stone. This study conducted tests at three points, namely the primary crusher, secondary crusher and tertiary crusher with a capacity of 50 tons/hour. Based on the measurement results, it is found that the highest vibration occurs in the horizontal direction of the secondary crusher machine seat where the displacement is 125.3 µm in the horizontal direction at 15 seconds, the largest velocity (Velocity) is 4.79 mm/s in the primary crusher. horizontal direction at the 45th second. and the magnitude of Acceleration (Acceleration) 1236 mm/s2 is found in the tertiary crusher vertical direction at the 45th second. According to the ISO 10816-3 standard, the vibration response results at the highest speed are 4.79 mm /s, categorized in zone B is light green, the vibration of the machine is good and can be operated without restrictions.